Serum trace element levels of liver cirrhosis and pancreatic cancer patients - H Sibel Karapinar; M Kürşat Türkdoğan; Fevzi Kiliçel (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
The incidence of liver cirrhosis and pancreatic cancer varies between countries and stands out as an important health problem worldwide. Liver cirrhosis is the most advanced stage of chronic liver disease and is a widespread result of chronic liver damage. The etiology of liver cirrhosis and pancreatic cancer, which are major causes of cancer fatalities in developed countries, is poorly understood. Many metabolic and physiological processes in the human body utilize trace elements. The creation and development of many diseases like cancer, cardiovascular, and diabetes mellitus occur with the disruption of trace element metabolism in the body as a result of improper nutrition, environmental, and occupational exposure, and impaired digestion and absorption. Methods and materials: In this study, copper (Cu), cadmium (Cd), iron (Fe), cobalt (Co), manganese (Mn), magnesium (Mg), nickel (Ni), zinc (Zn), and lead (Pb) concentrations were researched in the serum of liver cirrhosis and Pancreatic Cancer (PC) patients and healthy controls. Analysis of the elements was carried out by flame atomic absorption spectrophotometer. Results: Fe and Zn serum levels were considerably lower in individuals with liver cirrhosis and pancreatic cancer than in controls (p <0.001). Furthermore, mean serum levels of Cd and Mn in patients with liver cirrhosis and pancreatic Ca were considerably lower than in controls (p <0.01). In addition, when compared to pancreatic cancer, mean serum Cu and Ni levels in liver cirrhosis patients and controls were considerably lower (p <0.05). Mean serum levels of Pb in pancreatic Ca patients were significantly lower compared to liver cirrhosis patients and controls (p <0.05). When comparing all cancer patients to controls, mean serum Co and Mg levels were not substantially different. Conclusion: Deficiency in four trace elements (Cd, Mn, Fe, and Zn) was determined in patients with liver cirrhosis and pancreatic cancer. In addition, we have determined the deficiency of Cu and Ni trace elements (TEs) in pancreatic cancer patients. TE insufficiencies in cancer patients may be due to excessive consumption of foods and undernourishment. Epidemiological and physiological causes of trace element changes should be investigated further.